Arginine as host directed therapy in tuberculosis: insights from modulating arginine metabolism by supplementation and arginase inhibition - Qingkui Jiang; Ranjeet Kumar; Yi Zhao; Selvakumar Subbian; Lanbo Shi (One Health Advances)
Abstract Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a global health challenge. Arginine metabolism is central to immune responses, regulating nitric oxide (NO) production via inducible NO synthase (Nos2) and competing pathways mediated by arginases (Arg1 and Arg2). This study examines the impact of arginine supplementation and arginase inhibition during the acute phase of Mtb infection in mouse lungs, focusing on immune function, lung pathology, and mitochondrial function. Arginine supplementation enhanced Nos2 expression, promoted mitophagy, and supported angiogenesis and/or tissue repair by upregulating Vegfa. These mechanisms synergized to balance pro-inflammatory responses with tissue repair, improving immune defense while mitigating lung damage. In contrast, arginase inhibition disrupted Vegfa-mediated immune homeostasis, and impaired mitophagy, leading to exacerbated lung pathology. These findings underscore the complementary roles of Nos2 and arginase-mediated pathways in maintaining immune equilibrium during Mtb infection. Our results highlight arginine supplementation as a promising host-directed therapy for TB, capable of enhancing protective immunity and facilitating tissue repair. Conversely, caution is warranted for strategies targeting arginase due to potential adverse effects on inflammation resolution and mitochondrial quality control. Future studies should explore the long-term efficacy of arginine-based therapies and their integration with existing antibiotic regimens for optimal TB management.